Effects of Young Coconut Water Consumption on Blood Pressure in Menopausal Women with Hypertension: A Non-randomized Controlled Trial Study - Permatasari, Suci; Riyanto, Riyanto (Journal of International Multidisciplinary Research, 2024)
Hypertension is a non-communicable disease that is a global problem in both developed and developing countries and is the cause of stroke as the second death and third disability. Efforts are needed to reduce and control the prevalence of hypertension by utilizing nonpharmacological therapies, such as consuming young coconut water consumption. Therefore, this study aims to evaluate the effect of young coconut water consumption on reducing high blood pressure in menopausal women. A nonrandomized controlled trial study with a pretest-posttest control group design was chosen as the design of this study, which was conducted at the Community Health Center of Pekalongan, East Lampung Regency. A consecutive sampling technique was used to select eligible participants among menopausal women diagnosed with mild and moderate hypertension by medical personnel, totalling 16 treatment groups and 16 control groups.  The treatment group was given the intervention of consuming young coconut water 300 ml morning and evening for seven days and taking standard hypertension medication. Meanwhile, the control group took standard hypertension medication. Participants had their blood pressure checked using an aneroid tensimeter before and after treatment. Data were analysed using a paired t-test with a confidence level (α) of 0.05 to prove the treatment effect on blood pressure reduction. The results found that the treatment of drinking young coconut water affected reducing systole blood pressure (p-value 0.016) and diastole (p-value 0.007).  The average decrease in systolic and diastolic blood pressure pre and post-treatment was 11.25 mmHg and 9.87 mmHg after participants were controlled by taking standard hypertension medications. Drinking young coconut water can be used as a companion option for hypertension treatment by the community.